A technological model to define access to electronic clinical records. - Dalley, A. (IEEE Transactions on information technology in biomedicine)
This communication describes a functioning model that permits access to an electronic health record across a small number of providers resident in an Australian regional setting. Design criteria designated that provider access rights were to be assignable, revokable, transportable, and informable.